Co‐digestion of food waste and sewage sludge using the combination of a thermal alkali pre‐treatment and a two‐stage anaerobic digestion system. Issue 3 (1st June 2022) - Lee, Wonbae; Mo, Kyung; Park, Chul; Kim, Dokyun; Park, Seyong; Lee, Dongjin; Kwon, Junhwa; Kim, Moonil; Cui, Fenghao
Abstract: A thermal alkali pre‐treatment anaerobic digestion elutriated phased treatment (T‐ADEPT) was developed by combining the thermal‐alkali pre‐treatment (TAP) with the anaerobic digestion elutriated phased treatment (ADEPT) for the anaerobic co‐digestion of food waste (FW) and dewatered sewage sludge (SS). To improve the solubilization efficiency and methane yield, the optimal conditions for the TAP and ADEPT processes were identified. The soluble chemical oxygen demand (SCOD) solubilization, volatile suspended solids (VSS) reduction rate, volatile fatty acid (VFA) concentration, and methane yield all improved with our proposed process. The variations of the physical properties of the FW and SS mixtures confirm that the TAP process enhances the solubilization of organic matter. The methane yield of the T‐ADEPT process was 0.368 L CH4 /g VSadded, which was approximately 1.4 and 1.2 times higher than the values for a conventional two‐stage anaerobic digestion (AD) process and an AD process with pre‐treatment, respectively. These results show that the application of TAP and ADEPT processes using granular sludge can be an effective approach for the anaerobic co‐digestion of FW and SS. The proposed technique is more tolerant of the inhibitory effects of high concentrations of toxic compounds compared with a conventional two‐stage AD system. Modifying a conventional anaerobic digester has the potential to deliver low hydraulic retention times (HRTs) and high organic loading rates (OLRs). © 2022 Society of Chemical Industry (SCI).